THE BODY OF JESUS: Identifying the Eucharistic Presence - Anand, Subhash (Asian Horizons, 2016)
The article is prompted by two concerns. On the ecumenical front, the Roman Catholic doctrine concerning the presence of the Risen Lord in the Eucharist prevents us from accepting those who do not share our doctrine from participating fully in our Eucharist. In the pastoral field, many questionable practices result from the Roman doctrine. The article tries to go back to the New Testament and see whether the Roman Catholic doctrine is supported by the text common to all Christians. The author thinks that the New Testament texts do speak of a presence of Jesus with his community. This presence is interpreted in the breaking of bread: the Jesus who is present is the Jesus who broke himself for us and who invites us to break ourselves for others. Only in this way we can make him really present to ourselves and others.